2016
DOI: 10.5812/iranjradiol.37028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nasopalatine Canal Anatomic Variations Using Cone Beam Computed Tomography in a Group of Iranian Population

Abstract: Background: With regards to the increasing use of implants in the field of dentistry, the recognition of critical landmarks is essential. Nasopalatine canal (NPC) is one of these important indices, which due to high esthetic expectations in premaxilla, should be precisely evaluated before surgery. Objectives: This study aimed to evaluate the morphological and anatomical variations of the NPC. Materials and Methods: A total of 326 individual cone beam computed tomography (CBCT) images were analyzed in sagittal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 18 publications
(98 reference statements)
11
24
4
Order By: Relevance
“…However, NPC length did not show any significant difference with age in the current study. This result was in accordance with studies conducted by Thakur et al [42], Panjnoush et al [29], Acar and Kamburoglu [1] and Safi et al [36]. Liang et al [23], Etoz and Sisman [10], Ozcakir-Tomruk et al [28], and Song et al [38] reported that the individuals with teeth had more long NPC length than the edentulous subjects, which this was similar to our result.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, NPC length did not show any significant difference with age in the current study. This result was in accordance with studies conducted by Thakur et al [42], Panjnoush et al [29], Acar and Kamburoglu [1] and Safi et al [36]. Liang et al [23], Etoz and Sisman [10], Ozcakir-Tomruk et al [28], and Song et al [38] reported that the individuals with teeth had more long NPC length than the edentulous subjects, which this was similar to our result.…”
Section: Discussionsupporting
confidence: 93%
“…NPC length was statistically higher in males than females. This result was similar with previous studies [1,2,29,34,36,42,43]. The greater length of NPC in males than females may be due to the fact that males have relatively large craniocaudal dimensions [42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Males showed significantly more length as compared with females. Our results are in agreement with Safi et al 11 We found the effect of gender on measured dimensions of NPC. It was found that diam eter of nasal opening (A1), oral opening (A2), and width of the buccal bone plate over the oral opening (A4) were significantly higher in males as compared with females.…”
Section: Discussionsupporting
confidence: 83%
“…Failure in implantology has been frequently encountered that require implant removal and tissue augmentation. Implant contact with neurovascular tissue such as the nasopalatine canal might result in the 6,7,8 loss of osseointegration or development of sensory disturbances. In order to minimize complications following implant placement in the incisor area, proper image of the incisive canal and foramen before implant placement is highly important since it can help determine the morphology and position of the canal in relation to the surrounding structures.…”
Section: Introductionmentioning
confidence: 99%